The Critique of Sufism in Ahmad Amin’s Social Theory - Abdul Kadir Riyadi; Moh. Isom Mudin (Universitas Darussalam Gontor, 2020)
Ahmad Amin is renown for his reformist ideas. His thought covers a wide range of issues. Nonetheless, little has been done to study his perspective on Sufism. This paper is aimed at filling that gap. As a historian, sociologist and philosopher, Amin has many to offer concerning how Sufism should be treated. The paper argues that like many reformists, Amin is reluctant to accept certain –notably philosophical- aspects of Sufism and regard them as baseless, useless and ahistorical. These should be abandoned as they serve nothing for the Muslim community. His intellectual project is designed to dirent Sufism as a moral –that is Ghazalian- system. But he at the same time also proposes –like Ibn Khaldun- that Sufism should be treated as a means of realising commong good (maslahah) instead of acquiring personal sanctity (karamah). Hence, his critique of Sufism is based on the synthesis between Ghazalian form of paradigm with that of Khaldunian system of thought. While Amin has not paid enough attention to Sufism in his studies, deeper look at his world-view reveals that his interest to this spiritual dimension of Islam is unrivalled